Socialization of the Utilization of Plastic Waste into Crafts with Residents of RT 20, RW 05, Sawah Lebar, Bengkulu - Anisa Putri Pratama; Kriscin Gresia Hutabarat; Yunda Wulandari; Dimas Setiawan; Herlin Herlin; Lena Elfianty; Mimpira Haryono (Jurnal Pengabdian Mandiri, 2026)
This community service activity aims to increase awareness and practical skills of KKN-T period VI with residents in RT. 20 RW 05 Sawah Lebar in managing non-organic household waste. Through a participatory method involving material delivery and direct practice, participants were trained to recycle and reuse waste such as plastic wrappers and other packaging into useful handicrafts. The results of the activity showed that participants gained knowledge and confidence in managing non-organic waste creatively. The direct involvement model encouraged sustainable behavioral changes and aroused participants' interest in continuing craft practices independently at home. This training has proven effective in increasing environmental awareness and encouraging innovation in waste management at the household level.